Efeito antinociceptivo do salicilato de bornila em camundongos - Monte, Lucas de Oliveira (2014)
The pain is a serious public health problem, affects the quality of life of their patients, he brings harm to society. The science continues to seek new more potent analgesic drugs and with fewer side effects. Bornyl salicylate (BS) is a salicylic acid derivative obtained by esterification of salicylic acid with the monoterpene (-)-borneol, both with analgesic effects described in the literature. The aim of this study was to evaluate the antinociceptive effect of BS and its possible mechanisms in models of acute nociception in mice. For this purpose, we performed a behavioral pharmacological screening, test of acetic acid-induced writhing and formalin test. We used blockers pathways involved in pain in the formalin test to elucidate the possible mechanisms of action. BS (200 mg/kg, i.p.) showed behavioral changes indicative of CNS depressant drugs, no effect was observed on oral administration. Doses of 100 and 200 mg/kg (i.p.) reduced the number of writhings and increased the latency time to the first writhing. BS (100 and 200 mg/kg, i.p.) decreased paw licking time of animals only during the inflammatory phase of the formalin test. Pretreatment of animals with the precursor of nitric oxide (L-arginine, 600 mg/kg, i.p.), inhibitor of soluble guanylyl cyclase (methylene blue, 20 mg/kg, i.p.), non-selective muscarinic antagonist (atropine, 1 mg/kg, i.p.) and GABAA receptors antagonist (bicuculline, 1 mg/kg, i.p.), do not reverted the antinociceptive effect of BS (200 mg/kg, i.p.) in the second phase of the formalin test. These data suggest that BS exerts peripheral antinociceptive effect (anti-inflammatory), which mechanism seems in principle not involve nitric oxide, cGMP, muscarinic cholinergic receptors or GABAA receptors. Further studies are required to clarify the effect produced by bornyl salicylate.